Stanley Cavell, religion, and continental philosophy - Dahl, Espen, 1974- (Indiana series in the philosophy of religion., 2014)
The American philosopher Stanley Cavell (b. 1926) is a secular Jew who by his own admission is obsessed with Christ, yet his outlook on religion in general is ambiguous. Probing the secular and the sacred in Cavell's thought, Espen Dahl explains that Cavell, while often parting ways with Christianity, cannot dismiss it either. Focusing on Cavell's work as a whole, but especially on his recent engagement with Continental philosophy, Dahl brings out important themes in Cavell's philosophy and his conversation with theology.